Persaingan Akses Sumber Daya Air di Yeh Ho, Tabanan, Bali - Herlina Tarigan; Arya H. Dharmawan; SMP Tjondronegoro; Kedi Suradisastra (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2013)
EnglishSubak is a traditional Balinese water management organization with simple irrigation instruments, yet recognized as having high social resilience. This organization is not solely related to engineering elements, but also having socio-techno-religious characteristics. The politics of mass tourism development that promotes the development of infrastructures and public facilities by exploiting natural resources including land and water have caused land conversion and water utilization in a large scale, threatening the sustainability of subak. This research aims to examine the dynamics of water resource economic politics and its impact on subak institution which serves as one of the main pillar of development in Bali. Using a qualitative method, this research found that: (1) the politics of water economy was very dynamic, involving various local, national, and global actors with different interest and ideology; (2) the priority of mass tourism in Bali had led to a battle over access to water resources with both immaterial and material conflicts; (3) growth-oriented agricultural development had systematically reduced the socio-capital of subak; (4) the politics of development and the products of the state power (laws and policies) had systematically weakened the products of subak community power (awig-awig and perarem), so that the existence of subak as an irrigation organization that became the basis of strength for supporting food security was increasingly pressured.IndonesianSubak merupakan organisasi pengelola air khas Bali dengan alat irigasi yang sederhana namun diakui memiliki resiliensi sosial yang tinggi. Organisasi ini tidak semata-mata terkait dengan unsur-unsur keteknikan, melainkan bersifat sosial-tekno-religius. Politik pembangunan pariwisata massal yang memacu laju pembangunan infrastruktur dan fasilitas publik dengan pemanfaatan sumber daya alam termasuk lahan dan air menyebabkan alih fungsi lahan dan pemanfaatan air secara besar-besaran sehingga mengancam keberlangsungan subak. Penelitian ini bertujuan untuk mempelajari dinamika politik ekonomi sumber daya air dan dampaknya bagi kelembagaan subak yang menjadi salah satu pilar utama pembangunan di Bali. Penelitian dengan metode kualitatif ini menemukan bahwa: (1) politik ekonomi air sangat dinamis melibatkan beragam aktor lokal, nasional, global dengan kepentingan dan ideologi yang berbeda-beda; (2) prioritas pariwisata massal di Bali telah menyebabkan terjadinya pertarungan akses terhadap sumber daya air dengan konflik immaterial maupun material; (3) pembangunan pertanian yang berorientasi pertumbuhan secara sistematis telah mereduksi capital social subak; (4) politik pembangunan dan produksi kekuasaan negara (UU dan kebijakan) secara sistematis melemahkan produksi kekuasaan komunitas subak (awig-awig dan perarem) sehingga eksistensi subak sebagai organisasi pengairan yang menjadi basis kekuatan mendukung ketahanan pangan semakin terdesak.